2001
DOI: 10.1051/0004-6361:20000038
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy of the cluster of galaxies Abell 1795 with XMM-Newton

Abstract: Abstract. The initial results from XMM-Newton observations of the rich cluster of galaxies Abell 1795 are presented. The spatially-resolved X-ray spectra taken by the European Photon Imaging Cameras (EPIC) show a temperature drop at a radius of ∼200 kpc from the cluster center, indicating that the ICM is cooling. Both the EPIC and the Reflection Grating Spectrometers (RGS) spectra extracted from the cluster center can be described by an isothermal model with a temperature of ∼4 keV. The volume emission measure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
289
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 332 publications
(322 citation statements)
references
References 20 publications
32
289
1
Order By: Relevance
“…However, the COS G140L spectrum shows a weak positive residual at [Fe xxi], significant at 0.7σ, with a 90% upper limit on the integrated flux of 1.3 × 10 −16 erg s −1 cm −2 . The deprojected electron pressure at the location of this sightline is around 8 × 10 5 cm −3 K (Tamura et al 2001, Ettori et al 2002; with this assumption and an assumed Solar metallicity our upper limit on the effective path length of gas at 10 7.05 K is l < 23 kpc and the upper limit on the electron column density is Ne < 5 × 10 21 cm −2 .…”
Section: Other Sightlinesmentioning
confidence: 86%
“…However, the COS G140L spectrum shows a weak positive residual at [Fe xxi], significant at 0.7σ, with a 90% upper limit on the integrated flux of 1.3 × 10 −16 erg s −1 cm −2 . The deprojected electron pressure at the location of this sightline is around 8 × 10 5 cm −3 K (Tamura et al 2001, Ettori et al 2002; with this assumption and an assumed Solar metallicity our upper limit on the effective path length of gas at 10 7.05 K is l < 23 kpc and the upper limit on the electron column density is Ne < 5 × 10 21 cm −2 .…”
Section: Other Sightlinesmentioning
confidence: 86%
“…High resolution X-ray studies with XMM-Newton have recently shown that the soft X-ray spectra of several cooling flow clusters of galaxies are inconsistent with standard cooling flow models as the gas cools down to about 2-3 KeV, but not at lower temperatures Kaastra et al 2001;Tamura et al 2001;Molendi & Pizzolato 2001). How to reconcile cooling flow models with these observations is still matter of debate (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The pressure decrease in the core due to the cooling gas causes a net inflow toward the center of the cluster, hence the name cooling flow. XMM-Newton observations show that the amount of cool gas in the core of cooling-flow clusters is much lower than predicted (Peterson et al 2001;Kaastra et al 2001;Tamura et al 2001b;Peterson et al 2003;Kaastra et al 2004). Therefore, the standard cooling-flow model needs to be adjusted.…”
Section: Introductionmentioning
confidence: 98%